Дегазация рабочей жидкости гидравлического амортизатора - Oleg L'vovich Malomyzhev; Alexandr Georgievich Semenov; Vitaly Viktorovich Skutelinik (Вестник СибАДИ, 2017)
The analysis of the reasons causing reduction of effectiveness of the hydraulic suspension shock absorbers of the car which developed the new technology of their production. The Way of the fabrication of the hydraulic shock absorber is concluded in leading-in the shock absorber mask as worker to liquids with preliminary, before his(its) capsulation, measure on reduction of the separation of the gas from butter in process of the functioning(working) the shock absorber. Directly before leading-in from butter delete the gas, heating him(it) before the temperature above maximum worker and below the temperature of the flash, in particular before: T = (70-80) C° for liquid (the butters) AMG-10 (the GUEST 6794-75); T = (100-130) C° for liquids MGP-12 (THAT 38.301-29-40-97, slavol-AZH) and GRZH-12 (THAT 0253-048-0567-924-96); T = (130-145) C° for liquid (the butters) MOTUL Shock Oil Factory Line VI 400; T = (130-150) C° for liquid (the butters) AZH-12T (the GUEST 23008-78). Encapsulating the shock absorber realize before reduction of the temperature of the butter in him, at least once, before maximum worker. The Technical result to realization of the offer - increasing to efficiency and maintainability of the shock absorber.